Profil Meaning of Life Siswa Budaya Karo - Herda Fitri Br Ginting; Nur Hidayah; Blasius Boli Lasan (Graduate School of Universitas Negeri Malang, 2019)
Abstract: Meaning of life is values that are used as life guidelines, are important and valuable, sourced from comes from creative values, experential values, and attitudional values. Meaning of life involves all aspects of experience in an individual's life, involving every aspect of value, character, relationships with others, and also the way of life. Culture has a major role in the formation and fulfillment of the profile of the meaning of life of the Karo people. The study of the profile of the meaning of life of Karo culture was carried out through content analysis of the results of interviews with the Karo regional language teachers. Meaning of life Karo culture has eight values compiled according to three sources of value meaning of life.Abstrak: Meaning of life adalah nilai-nilai yang dijadikan pedoman hidup, bersifat penting, berharga, serta bersumber dari creative values, experential values, dan attitudional values. Meaning of life melibatkan seluruh aspek pengalaman dalam hidup individu, melibatkan setiap aspek nilai, karakter, hubungan dengan orang lain, dan cara hidup. Budaya memiliki peran utama dalam pembentukan dan pemenuhan profil. meaning of life masyarakat Karo. Pengkajian profil meaning of life budaya Karo dilakukan melalui analisis isi terhadap hasil wawancara terhadap guru bahasa daerah Karo. Meaning of life budaya Karo memiliki delapan nilai yang disusun sesuai tiga sumber nilai meaning of life.